The Impact of Transfer of Cacao Commodities to Corn on Farmers 'Income in Bangsala Village, Porehu Sub-District North Kolaka District - Maripadang, Werni; Yunus, Lukman; Rosmawaty, Rosmawaty (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2021)
The purpose of this study was to determine the factors causing the transfer of commodity cocoa to maize in Bangsala Village, Porehu Sub District, North Kolaka District, and the impact of commodity transfer of cocoa to corn on farmers' income. The research location was determined with the consideration that Bangsala Village had the largest number of farmer households that shifted commodities compared to other villages. The number of samples in this study was 49 people while the methods used in this study were descriptive analysis, income analysis, and t-test. The results showed that the factors that influenced the farmers to switch from cocoa commodities to corn were technical factors including hard cacao care, pests and diseases that were difficult to control, and the old age of the cocoa plants. Economic factors include low selling prices, lower production, and low-profit rates. Social factors include seeing the success of friends, following friends, and their own beliefs. The impact of the conversion of cocoa commodities to corn is seen in the increased income of farmers, farmers have additional income from their cocoa plantations, namely corn plants. It is clear here that the conversion of cocoa plant commodities to corn has a positive impact on the community in Bangsala Village, Porehu District, North Kolaka Regency. The sig (2-tailed) value is 0.000 <0.05, that is, there is a significant difference between the income of the respondent farmers on the cornfield and on the cocoa field, thus the commodity transfer affects the farmer's income